2009
DOI: 10.4012/dmj.28.20
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical surface modification of titanium in dentistry

Abstract: Titanium and its alloys have good biocompatibility with body cells and tissues and are widely used for implant applications. However, clinical procedures place more stringent and tough requirements on the titanium surface necessitating artificial surface treatments. Among the many methods of titanium surface modification, electrochemical techniques are simple and cheap. Anodic oxidation is the anodic electrochemical technique while electrophoretic and cathodic depositions are the cathodic electrochemical techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
92
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 71 publications
0
92
0
5
Order By: Relevance
“…5,6 Additionally, differences in porosity allow for potential drug incorporation and release around titanium implants. 7,8 However, to improve biological stability, changes in the unique surface characteristics should be minimal during self-tapping or self-drilling insertion through cortical bone, during which the miniscrew is exposed to friction and heat. For example, shiny spots appear at the sandblasted large-grit, acid-etched (SLA) surface when damaged during the handling or packaging process, or when removed from the sterile ampule.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Additionally, differences in porosity allow for potential drug incorporation and release around titanium implants. 7,8 However, to improve biological stability, changes in the unique surface characteristics should be minimal during self-tapping or self-drilling insertion through cortical bone, during which the miniscrew is exposed to friction and heat. For example, shiny spots appear at the sandblasted large-grit, acid-etched (SLA) surface when damaged during the handling or packaging process, or when removed from the sterile ampule.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Numerous attempts to improve osteointegration of Ti implants have been attempted with varying degrees of success. 16,17 Recent attention has been focused on the immobilization of small bioactive molecules on the implant surface. 18,19 For example, RGD (Arg-GlyAsp), another cell attachement peptide which binds the integrin receptor, has been reported to promote osteoblast attachment.…”
mentioning
confidence: 99%
“…On the other hand, Kim and Ramaswamy [27] observed the appearance of microcracks in the oxides with the increase of the electrolyte concentration. However, in the present research, the most significant changes in morphology were observed with the increase of the voltage with each concentration of H2SO4 used, but not with the increase of the concentration independent of the voltage.…”
Section: Color Of the Coatingsmentioning
confidence: 99%